PENGARUH PARTISIPASI PENYUSUNAN ANGGARAN TERHADAP KINERJA MANAJERIAL DENGAN KOMITMEN ORGANISASI DAN LOCUS OF CONTROL SEBAGAI VARIABEL MODERATING - Livia Alhabsyie; Moh. Amin; Junaidi Junaidi (e_Jurnal Ilmiah Riset Akuntansi, 2019)
ABSTRACTThis research was conducted to analyze "The Effect of Budgetary Participation in Managerial Performance with Organizational Commitment as Moderating Variables". The sample in this study were managers and employees at PT. Muria Sumba Manis NTT. The analytical method is Multiple Linear Regression with SPSS 22 For Windows Software. The simultaneous participation in budgeting, organizational commitment and locus of control has an effect on managerial performance. Partially the Effect of Budgetary Participation does not affect managerial performance while Organizational Commitment and Locus of Control have an effect on Managerial Performance and Moderating variables. Keywords: Budget Participation, Managerial Performance, Organizational Commitment, Locus Of Control